2021
DOI: 10.3389/fnagi.2021.647015
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Inflamma-miRs as Potential Biomarkers of Cognitive Impairment in Patients Affected by Alzheimer’s Disease

Abstract: Alzheimer’s disease (AD), the most prevalent neurodegenerative disease in the growing population of elderly people, is still lacking minimally-invasive circulating biomarkers that could facilitate the diagnosis and the monitoring of disease progression. MicroRNAs (miRNAs) are emerging as tissue-specific and/or circulating biomarkers of several age-related diseases, but evidence on AD is still not conclusive. Since a systemic pro-inflammatory status was associated with an increased risk of AD development and pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 60 publications
0
16
0
Order By: Relevance
“…Therefore, serum miR-146a-5p level may be a circulating marker of the efficacy of the anti-inflammatory response and thus of the susceptibility to develop complications. Consistent with this, miR-146a-5p is a well-established marker of inflammation and is associated with a variety of immune and non-immune inflammatory conditions [ 14 , 43 45 ], including CVD, Alzheimer’s disease, and type 2 diabetes [ 34 , 46 49 ].…”
Section: Discussionmentioning
confidence: 76%
“…Therefore, serum miR-146a-5p level may be a circulating marker of the efficacy of the anti-inflammatory response and thus of the susceptibility to develop complications. Consistent with this, miR-146a-5p is a well-established marker of inflammation and is associated with a variety of immune and non-immune inflammatory conditions [ 14 , 43 45 ], including CVD, Alzheimer’s disease, and type 2 diabetes [ 34 , 46 49 ].…”
Section: Discussionmentioning
confidence: 76%
“…For instance, AD patients were accurately distinguished from healthy controls based on the downregulation of miR-9-5p in whole-blood samples (Souza et al, 2020). Giuliani et al (2021) evaluated the plasma levels of miR-17-5p, miR-21-5p, and miR-126-3p in a cohort of AD patients and found that they were significantly upregulated compared to those of healthy controls. Additionally, cases of mild and severe cognitive impairment could also be discriminated based on the level of miR-126-3p expression (Giuliani et al, 2021).…”
Section: Inflamma-micrornas As Diagnostic Biomarkers For Alzheimer's Diseasementioning
confidence: 99%
“…Giuliani et al (2021) evaluated the plasma levels of miR-17-5p, miR-21-5p, and miR-126-3p in a cohort of AD patients and found that they were significantly upregulated compared to those of healthy controls. Additionally, cases of mild and severe cognitive impairment could also be discriminated based on the level of miR-126-3p expression (Giuliani et al, 2021). Moreover, analyses of the expression profile of inflamma-miRNAs demonstrated that plasma miR-34a and miR-146a levels, as well as CSF miR-34a, miR-125b, and miR-146a levels in AD patients were significantly lower than those in control subjects.…”
Section: Inflamma-micrornas As Diagnostic Biomarkers For Alzheimer's Diseasementioning
confidence: 99%
“…MiR-21 can inhibit cell apoptosis induced by Aβ 1−42 via modulating cell death protein 4 (PDCD4) /phosphatidylinositol 3-kinase PI3K/AKT/GSK-3β pathway in the CNS (Feng et al, 2018 ). Meanwhile circulating miR-21-5p was significantly upregulated in the plasma of AD patients and was negatively correlated to cognitive impairment (Giuliani et al, 2021 ). Simultaneously, disturbed level of miR-21 was observed in diverse neuropathic pain models (Zhong et al, 2019 ) where it targets metalloproteinase-3 (TIMP3) and chemokines C-C motif ligand 1 (CCL1) that consequently evoke cytokine production of TNF-α, IL-1β, and IL-6 and aggravate neuroinflammation.…”
Section: Pain: the Underestimated Companion In Alzheimer's Disease?mentioning
confidence: 99%